O psicólogo no contexto da saúde pública: uma análise sobre o bem-estar e a satisfação no trabalho - Sousa, Alline Alves de (2011)
The researchers interest for the well-being at work and job satisfaction has strongly increased as well as the insertion of psychologists in health teams. The main targets of this study were to identify the perceived factors related to well-being as well as verify the influence of personal variables, professional variables such as the employing institution and the job satisfaction about the well-being at work of psychologists being civil servants in the public health area working with psychotherapy. The sample was composed of 66 psychologists at two health secretaries and one federal university. As instrument it was elaborated a questionnaire of personal, professional, employer data, scales to measure job satisfaction and well-being at work, besides two open questions to identify factors that contribute to the wellbeing at work and the factors which cause any harm. Statistical analysis of quantitative data were done through SPSS for Windows software and open questions were analyzed separately through content analysis. The answers about the well-being factors were grouped into categories and were predominant in relation to good relationship, the feeling of reaching and the patient as promoters of well-being, while management problems, with the team and working conditions were mostly referred to as harmful to well-being. Correlation tests showed that all satisfaction factors correlated significantly with different factors of well-being at work, the results showed correlation significant only between the service time and negative affection. Analysis of multiple regression for explanation test of the factors of well-being at work showed that explicative variable of well-being were the satisfaction with their participation in the job and satisfaction with working conditions, with 39% to 51% of variance explained through these factors. The study made it possible to describe the profile of psychologists who work at public health service, identify the most important factors related to their well-being at work and demonstrate the adequation of the proposed model relating job satisfaction with well-being at work. It was possible to suggest some actions of practical order to improve the work of these professionals. However, any change in this sense must be supported by knowledge of empirical origin and must be followed by an evaluation of its impact on well-being levels of the team and on the quality of public services of mental health.